2006
DOI: 10.1080/09712119.2006.9706587
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Hydrated Sodium Calcium Aluminosilicate and Vermiculite for Aflatoxin B1Adsorption in Pacific White Shrimp(Litopenaeus vannamei)Diets

Abstract: Suppadit, T., Jaturasitha, S. and Pripwai, N. 2006

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
4
0
3
Order By: Relevance
“…In vitro and in vivo studies have shown that hydrated sodium calcium alumino-silicates (HSCAS, Döll et al 2005), montmorillonites (Ramos and Hernández 1996), bentonites (Schell et al 2000), and zeolites (Piva et al 1995) have a high binding affinity for aflatoxins. Two studies using aluminosilicates in diets for Pacific white shrimp, Litopenaeus vannamei, failed to demonstrate the elimination of negative effects from aflatoxins (Suppadit et al 2006). The same was reported for the black tiger shrimp, Penaeus monodon (Soonngam and Hutacharoen 2007).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…In vitro and in vivo studies have shown that hydrated sodium calcium alumino-silicates (HSCAS, Döll et al 2005), montmorillonites (Ramos and Hernández 1996), bentonites (Schell et al 2000), and zeolites (Piva et al 1995) have a high binding affinity for aflatoxins. Two studies using aluminosilicates in diets for Pacific white shrimp, Litopenaeus vannamei, failed to demonstrate the elimination of negative effects from aflatoxins (Suppadit et al 2006). The same was reported for the black tiger shrimp, Penaeus monodon (Soonngam and Hutacharoen 2007).…”
Section: Introductionmentioning
confidence: 83%
“…En estudios in vitro e in vivo se ha mostrado que los aluminosilicatos de calcio y sodio hidratados (HSCAS por sus siglas en inglés, Döll et al 2005), las montmorillonitas (Ramos y Hernández 1996), las bentonitas (Schell et al 2000) y las zeolitas (Piva et al 1995) tienen una alta afinidad por las aflatoxinas. Dos estudios que usaron aluminosilicatos en dietas para el camarón blanco del Pacífico, Litopenaeus vannamei, no pudieron demostrar la eliminación de los efectos negativos de las aflatoxinas (Suppadit et al 2006). Lo mismo se documentó para el camarón tigre, Penaeus monodon (Soonngam y Hutacharoen 2007).…”
Section: Aluminosilicate-based Productsunclassified
See 2 more Smart Citations
“…Removal of aflatoxins from feed is a challenge that demands innovative decontamination technologies (Oguz, Kurtoglu, & Coskun, 2000;Williams et al, 2004). In aquaculture, popular strategies are based on the addition of adsorbent clay minerals to feed, among them bentonites or montmorillonite (Ellis, Clements, Tibbetts, & Winfree, 2000;Hassan, Kenawy, Abbas, & Abdel-Wahhab, 2010;Zychowski et al, 2013), other clays labelled as hydrated sodium aluminosilicates and vermiculite (Arana et al, 2011;Arunlertaree, Soonngam, & Hutacharoen, 2007;Suppadit, Jaturasitha, & Pripwai, 2006) and mixtures of minerals and Saccharomyces cerevisiae yeast (Selim, El-hofy, & Khalil, 2014;Staykov, Spring, Denev, & Sweetman, 2007). These adsorbents claim to reduce the exposure of aflatoxins in the gut by interfering with its bioavailability, hence limiting toxin absorption to the blood and tissues.…”
mentioning
confidence: 99%